Non-convulsive status epilepticus: an often-overlooked etiology of syndrome of inappropriate antidiuretic hormone secretion - Davis, Elizabeth; Chakraborty, Rima (International Journal of Research in Medical Sciences, 2017)
Altered mental status is a common presenting complaint in adult medicine with a broad differential diagnosis. When found in the context of chronic medical conditions, less common etiologies can be overlooked. We present a case of acute altered mental status thought to be secondary to acute on chronic hyponatremia in the context of syndrome of inappropriate antidiuretic hormone secretion (SIADH), eventually diagnosed as non-convulsive status epilepticus, partial type. We report the case of a 67-year-old patient with known SIADH of unknown etiology, hypertension, chronic pancreatitis and chronic obstructive pulmonary disease (COPD) who presented with fatigue, myalgia, decreased urine output. On presentation patient also had profound acute on chronic hyponatremia. During sodium correction, the patient developed an acute, progressive decline in mental status. Vital signs remained stable and workup including LP and MRI were negative. Initial electroencephalographic (EEG) showed no definitive seizure activity, but did show bifrontal focal continuous slowing. The patient’s mental status continued to decline and upon further evaluation it was suggested that the EEG findings and the patient’s progressive AMS could be compatible with non-convulsive status epilepticus. The patient received loading doses of IV lorazepam and levetiracetam and within 48 hours after initial treatment was back to baseline. Non-convulsive status epilepticus is a common, but heterogeneous subclass of status epilepticus that is difficult to diagnose. This case demonstrates the difficulty of diagnosing normalized corrected Shannon entropy (NCSE) in the context of other chronic medical conditions and the importance of including it on any differential diagnosis for acute change in mental status.